USM TO HOST PUBLIC TALK BY NOBEL LAUREATE PROF. DR. SHUJI NAKAMURA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 22 July 2016 – Universiti Sains Malaysia (USM) will host a public talk by the Nobel Prize Winner in Physics 2014, Professor Dr. Shuji Nakamura at the Dewan Pembangunan Siswa 1, Kompleks Cahaya Siswa on Friday, 29 July 2016 at 10.00 a.m.